Correction of the typification of Corydalis solida var. bracteosa and lectotypification of C. densiflora (Papaveraceae) - Conti, Fabio; Uzunov, Dimitar; Bartolucci, Fabrizio (Phytotaxa, 2015)
The genus Corydalis DC. in Lamarck & Candolle (1805: 637) (Papaveraceae) consists of about 440 species distributed in Eurasia, North America and Africa (Lidén & Zetterlund 1997). Corydalis densiflora C.Presl in Presl & Presl (1822: 10) was first described from Sicily based on material collected by C.B. Presl “in nemorosis Nebrodum” during a trip in Sicily in 1817 (Sutorý 2006). According to Lidén & Zetterlund (1997), C. densiflora occurs in peninsular Italy, Sicily and Algeria. The plants coming from Algeria have also been described as C. solida (Linnaeus 1753: 699) Clairville (1811: 371) var. bracteosa Battandier & Trabut (1905: 498), a taxon regarded by Lidén & Zetterlund (1997) as a synonym of C. densiflora. The aim of this paper is to identify and study the type material of both names and to clarify their distribution. This study was carried out within the initiative “Italian Loci Classici Census” (Domina et al. 2012, Peruzzi et al. 2015), aimed at providing data on the original material of the plants described from Italy (e.g. Di Pietro et al. 2012, Gallo et al. 2012, Peruzzi et al. 2012, 2013a, 2013b, Bartolucci & Conti 2013, Bartolucci et al. 2013, Bartolucci & Peruzzi 2014, Bartolucci & Domina 2014, Conti et al. 2014).